2017
DOI: 10.24036/ld.v7i1.3531
|View full text |Cite
|
Sign up to set email alerts
|

Students’ Perception Toward Their Reading Difficulties of Different Genres

Abstract: Students of English Language Teaching Program are  required to have the ability to comprehend different kinds of texts or genres. Howewer, their reading ability as reflected in Reading courses and other courses is low. This paper is aimed at describing the students’ perception toward their reading difficulties of different genres. The data presented in this paper are partially derived from the data collected through a descriptive research conducted in 2009/2010 at the English Department of FBSS, State Universi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 3 publications
1
4
0
Order By: Relevance
“…The finding concerning the partial contribution of genre awareness to reading comprehension confirms the results of the previous studies (e.g. from Andriyani et al, 2019;Azizah & Fahriany, 2017;Grabe, 2012;Hansen, 2018;Kalali & Pishkar, 2015;Karbelaei & Hajezi, 2015;Molotja & Themane, 2018;Nam, 2014;Rozimela, 2014;Sari, 2017;Sawangsamutchai & Rattanavich, 2016;To & Pang, 2019;Xu & Li, 2018;Yayli, 2011). In general, these previous studies led to several findings.…”
Section: Genre Awareness and Reading Comprehensionsupporting
confidence: 89%
See 4 more Smart Citations
“…The finding concerning the partial contribution of genre awareness to reading comprehension confirms the results of the previous studies (e.g. from Andriyani et al, 2019;Azizah & Fahriany, 2017;Grabe, 2012;Hansen, 2018;Kalali & Pishkar, 2015;Karbelaei & Hajezi, 2015;Molotja & Themane, 2018;Nam, 2014;Rozimela, 2014;Sari, 2017;Sawangsamutchai & Rattanavich, 2016;To & Pang, 2019;Xu & Li, 2018;Yayli, 2011). In general, these previous studies led to several findings.…”
Section: Genre Awareness and Reading Comprehensionsupporting
confidence: 89%
“…Similarly, Kalali and Pishkar (2015) find that awareness of genre can improve students' reading comprehension. Some other studies also confirm the contribution of genre awareness to students' reading comprehension without mentioning the extent to which genre awareness can aid reading comprehension (Molotja & Themane, 2018;Sari, 2017;Sawangsamutchai & Rattanavich, 2016;Xu & Li, 2018;Yayli, 2011). The significant role of genre awareness on students' reading comprehension is emphasized by Sari (2017), who conducted a study on university students as she found that students who were not aware of genres had problems in reading comprehension.…”
Section: Genre Awarenessmentioning
confidence: 96%
See 3 more Smart Citations